Lifestyles and health behaviours of young adults with type 1 diabetes in Portugal. 2017 - Nabais, Joao (2017)
Participants reported satisfaction with life as 6.6 ±1.7 (scale 0-10). Most of young adults show good adherence to dietary intake (83%), insulin therapy (83%) and glucose monitoring (73%), but only one third practice recommended physical activity. We verified positive statistically significant correlation between adherence to nutrition, insulin therapy and glucose monitoring. Youngsters present 8.7 ±1.6% as mean value for HbA1c. Highest HbA1c levels were correlated to less global adherence to diabetes treatment, perception of health, satisfaction with life and psychological adaptation to diabetes. 25% present diabetes complications. The best representations about diabetes were positively correlated with adherence to nutrition and insulin therapy. Youngsters with better psychological adaptation to diabetes have better adherence to diabetes treatment relating to nutrition, insulin therapy and glucose monitoring. They reported good social support and referred the benefits of group activities with peers.